An unusual case of stabbing chest pain …literally: a case report. Issue 7 (8th July 2022) - Santos, João; Neto, Vanda; Marmelo, Bruno; Correia, Miguel
Abstract: Background: Cardiac surgery is associated with a significant risk of potential postoperative complications. We describe a case of a patient with an unusual late cardiac perforation caused by a needle used to fix temporary epicardial pacing wires to the skin, which slowly migrated across subcutaneous tissues for 2 years following postoperative period. Case summary: We report a case of middle-aged woman admitted to the cardiac intensive care unit due to suspected acute myocardial infarction. Multimodality imaging revealed the presence of an unusual intracardiac foreign body, located inside the interventricular septum and perforating towards the left atria, complicated by a small intracardiac fistula between septal coronary branches and the right ventricle. Analysis of previous examinations revealed that a needle used to fix temporary epicardial pacing wires to the skin had been left inside the patient, beneath the level of the diaphragm, after cardiac surgery in 2018. This foreign body slowly migrated across the diaphragm, towards the mediastinum, finally lodging inside the heart, after a period of 3 years. The patient was referred to cardiac surgery for foreign body retrieval. Discussion: We describe an unusual case of cardiac perforation caused by a needle used to fix these wires to the skin, which migrated across subcutaneous tissues and finally lodged inside the basal interventricular septum and left atria. Full compliance with standardized surgical care bundles, as well as the implementation of a structured incident reporting system, is of upmost importance to prevent postoperative complications and improve surgical care.